2020
DOI: 10.1186/s12879-020-05136-x
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated Mycobacterium abscessus subsp. massiliense infection in a Good’s syndrome patient negative for human immunodeficiency virus and anti-interferon-γ autoantibody: a case report

Abstract: Background: Good's syndrome (GS) is characterized by immunodeficiency, and can lead to severe infection, which is the most significant complication. Although Mycobacterium rarely causes infection in patients with GS, disseminated nontuberculous mycobacterial (NTM) infection frequently occurs in GS patients that are also positive for the human immunodeficiency virus (HIV) or anti-interferon (IFN)-γ autoantibodies. Here, we report a rare case of GS with NTM without HIV or IFN-γ autoantibodies. Case presentation:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“… 7 SFTX is a novel respiratory quinolone that is reportedly often used for patients with severe M. abscessus infection as an alternative and/or adjuvant to standard antibiotic regimens. 10 SFTX generally shows 2- to 16-fold higher antimicrobial effects compared with previous new quinolones, such as LVFX and ciprofloxacin. 7 In our cases, SFTX showed both microbiological susceptibility ( Table 1 ) and clinical efficiency in all patients, suggesting its usefulness as outpatient treatment for M. abscessus infection in combination with CAM.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“… 7 SFTX is a novel respiratory quinolone that is reportedly often used for patients with severe M. abscessus infection as an alternative and/or adjuvant to standard antibiotic regimens. 10 SFTX generally shows 2- to 16-fold higher antimicrobial effects compared with previous new quinolones, such as LVFX and ciprofloxacin. 7 In our cases, SFTX showed both microbiological susceptibility ( Table 1 ) and clinical efficiency in all patients, suggesting its usefulness as outpatient treatment for M. abscessus infection in combination with CAM.…”
Section: Discussionmentioning
confidence: 91%
“…massiliense . 10 He also had type 2 DM, and the correlation between an immunosuppressed status, including DM, and severe M. abscessus infection as an opportunistic infection was suggested. It was previously reported that non-classical monocytes from obesity-based DM and non-obese tuberculosis patients exhibit similar activation profiles (CD86/CD206/TLR-2 and TLR-4 expressions), and serum adiponectin levels increased similarly in tuberculosis and obesity-based DM patients.…”
Section: Discussionmentioning
confidence: 99%
“…In IEI patients, type I IFN autoantibodies were reported for APS-1 patients ( 14 ). Although described previously ( 38 , 39 ), impact of type I IFN autoantibodies on the high case fatality rate in Good’s syndrome was never examined.…”
Section: Discussionmentioning
confidence: 99%
“…In most cases where diabetes is reported, it is described as an underlying disease, but details on adjunctive tests and glycemic control are seldom provided. It appears that the onset of diabetes is independent of GS [ [48] , [49] , [50] ]. Latent autoimmune diabetes in adults (LADA) was first described by Tuomi et al, in 1993 [ 51 ] as having phenotypical characteristics similar to type 2 diabetes and immunological features akin to type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%